Phenotypic and Genetic Features that Differ Between Hereditary and Sporadic Melanoma: Results of a Preliminary Study from a Single Center from Turkey - Çakır, Aysel; Elcin, Gonca; Kilickap, Saadettin; Gököz, Özay; Taskiran, Zihni Ekim; Celik, İsmail (Dermatology Practical & Conceptual, 2023)
Introduction: We have observed that most cutaneous melanoma patients under our supervision lack characteristic phenotypical features for melanoma. In contrast; history of cancers other than melanoma and age at onset before 50 were common. This observation was in favour of hereditary melanoma. Objectives: The aim of this study was to search for the phenotypical and genetic features that distinguish between sporadic and hereditary melanomas. Methods: All cutaneous melanoma patients (n=43) under our supervision were evaluated dermatologically in detail for phenotypical features. CDKN2A and MC1R mutations were detected with Sanger sequencing method. Assignment to hereditary and sporadic groups was done according to the "melanoma cancer syndrome assessment tool". Patients who were diagnosed before 50 years of age were also assigned to the hereditary melanoma group. Results: Concerning phenotypic features, fair eye colour was statistically significantly higher in the sporadic group (p=0.000). CDKN2A was detected in only 1 patient in the hereditary group. MC1R mutations were found in 12 out of 13 (92.3%) in the hereditary melanoma group with a score ≥3 points, 13 out of 18 (72.2%) in the early onset group and 5 out of 12 (41.7%) in the sporadic melanoma group (p=0.024). Discussion: Incidence of CDKN2A mutations in our hereditary group is in accordance with reported incidences from Mediterranean countries. The difference between the hereditary and sporadic melanoma groups in terms of MC1R mutations supports the idea that MC1R genetic testing might help to determine patients with higher risk for hereditary melanoma.